FEATURES OF BRAND STRATEGY DEVELOPMENT FOR AGRICULTURAL ENTERPRISES - GALCHYNSKA, Julia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the specifics of the development and stages of a brand strategy for agricultural enterprises, the essence and meaning of the concept of "brand strategy" from conceptual point of view, highlights the main development vectors and trends of foreign experience and Ukraine. The purpose of the article is to determine the content and main stages of formation of a brand strategy for agricultural enterprises, structuring elements and its tendency to change in agrarian enterprises. The influence of modern agricultural innovations on the marketing of the brand of agricultural products is analyzed. It has been proven that the development of a brand strategy for agricultural enterprises depends on many factors, namely on a quick response to price fluctuations, the organization of optimal logistics channels for the sale of agricultural products, on a quick response to changes in the main market trends. Modern approaches to the process of developing marketing strategies of agricultural enterprises and methods of marketing strategic analysis are considered.The peculiarities of agribusiness in Ukraine are: lack of long-term vision, market awareness, brand awareness is relatively weak. Brand in the field of production and business areas and not enough attention. In particular, farmers scattered business, a low degree of organization even if the registration of the trademark brand, but also unable to carry out publicity and the corresponding market development, resulting in increased awareness of trademark awareness, can not play the role of the brand. The core of agricultural product brand building is brand quality construction. The implementation of agricultural standardization is the guarantee of agricultural brand. However, compared with foreign developed countries, Ukraine agricultural standardization level is low, the implementation of agricultural standards lag. Many places only focus on standard-setting, and not pay attention to the implementation of standards, production, processing and other links are still conventional production. This caused the quality of agricultural products at different levels, seriously hampered the cultivation and development of well-known agricultural products brand.The main steps of building a brand strategy include defining the target audience, creating a unique offer in the market, a compelling message and an attractive visual identity. When building brand strategies of agricultural enterprises, the principles of uniqueness of product offers and expressive naming should be followed. Conclusions are drawn on the main regarding the effective development and use of brand strategy for agricultural enterprises and product.
Keywords: brand; strategy; marketing; agriculture; agricultural enterprises